Changes in H+, K+, and Ca2+ Concentrations, as Observed in Seizures, Induce Action Potential Signaling in Cortical Neurons by a Mechanism That Depends Partially on Acid-Sensing Ion Channels - Alijevic, Omar; Peng, Zhong; Kellenberger, Stephan (Frontiers in Cellular Neuroscience, 2021)
Acid-sensing ion channels (ASICs) are activated by extracellular acidification. Because ASIC currents are transient, these channels appear to be ideal sensors for detecting the onset of rapid pH changes. ASICs are involved in neuronal death after ischemic stroke, and in the sensation of inflammatory pain. Ischemia and inflammation are associated with a slowly developing, long-lasting acidification. Recent studies indicate however that ASICs are unable to induce an electrical signaling activity under standard experimental conditions if pH changes are slow. In situations associated with slow and sustained pH drops such as high neuronal signaling activity and ischemia, the extracellular K+ concentration increases, and the Ca2+ concentration decreases. We hypothesized that the concomitant changes in H+, K+ and Ca2+ concentrations may allow a long-lasting ASIC-dependent induction of action potential (AP) signaling. We show that for acidification from pH7.4 to pH7.0 or 6.8 on cultured cortical neurons, the number of action potentials and the firing time increased strongly if the acidification was accompanied by a change to higher K+ and lower Ca2+ concentrations. Under these conditions, APs were also induced in neurons from ASIC1a-/- mice, in which a pH of ≤ 5.0 would be required to activate ASICs, indicating that ASIC activation was not required for the AP induction. Comparison between neurons of different ASIC genotypes indicated that the ASICs modulate the AP induction under such changed ionic conditions. Voltage-clamp measurements of the Na+ and K+ currents in cultured cortical neurons showed that the lowering of the pH inhibited Na+ and K+ currents. In contrast, the lowering of the Ca2+ together with the increase in the K+ concentration led to a hyperpolarizing shift of the activation voltage dependence of voltage-gated Na+ channels and to an increase in their current amplitude. We conclude that the ionic changes observed during high neuronal activity mediate a sustained AP induction caused by the potentiation of Na+ currents, a membrane depolarization due to the changed K+ reversal potential, the activation of ASICs, and possibly effects on other ion channels. Our study describes therefore conditions under which slow pH changes induce neuronal signaling by a mechanism involving ASICs.